Nerve high‐resolution ultrasonography in tangier disease. Issue 5 (7th February 2019) - Pasquale, Antonella Di; Leonardi, Luca; Fionda, Laura; Vanoli, Fiammetta; Garibaldi, Matteo; Inghilleri, Maurizio; Ceccanti, Marco; Cambieri, Chiara; Onesti, Emanuela; Antonini, Giovanni
ABSTRACT: Introduction : Tangier disease (TD) is an autosomal recessive disorder characterized by severe reduction in high‐density lipoprotein and accumulation of cholesterol esters in peripheral nerves and other tissues. The aim of this study was to evaluate whether nerve high‐resolution ultrasonography (HRUS) can detect morphological nerve changes in TD. Methods : Three related patients of a previously reported Italian family with Tangier disease, carrying the Y1698X mutation in ABCA1, underwent clinical, neurophysiological, and quantitative nerve HRUS evaluation. Nerve HRUS data were compared with normal controls. Results : Despite neurophysiological abnormalities, no quantitative HRUS abnormality was detected in peripheral nerves. Discussion : Normalcy of HRUS in neurophysiologically abnormal nerves suggests possible subtle abnormalities that escape quantitative HRUS detection. Systematic studies in larger TD cohorts with different mutations are needed to confirm our findings. Muscle Nerve 59:587–587, 2019